A Dialectical Social Framework for the Analysis of Media Communication - Ercan Gündoğan (Türkiye İletişim Araştırmaları Dergisi)
This article proposes a dialectical theoretical framework for the analysis of media and mediacommunication. The study begins with the determination that a genuine theoretical analysis of mediaand communication must take into account certain constitutive relations and processes within thesocial whole, since communication is not part of a single social structure or a distinctive structurewithin a social system. The article tries to formulate and analyze these relationships and processes inthe form of dialectical tensions and patterns created by simultaneous, twin and overlapping dialecticrelationships and processes of individualization-socialization and classification-massization. In doingso, the article reinterprets the forms of old and new media and of communication and highlights blogsas they reveal a true communicative media potential; the article also discusses concepts such as “freelabor”, which is also used by those who approach communication and media issues from politicaleconomy, and proposes new concepts such as virtual class and virtual petty bourgeoisie.